Sipri yearbook 2013 : armaments, disarmament and international security - Institute, Stockholm International Peace Research ([S.l.] : Oxford University Press, 2013)
The 44th edition of the SIPRI Yearbook analyses developments in 2012 in Security and conflicts Military spending and armaments Non-proliferation, arms control and disarmament The SIPRI Yearbook contains extensive annexes on the implementation of arms control and disarmament agreements and a chronology of events during the year in the area of security and arms control. Purchasers of the print edition will also be able to access the Yearbook online.
Keywords: Arms control; Disarmament